Partikel Majemuk To Doujini Dan To Tomoni Dalam Kalimat Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini (KIRYOKU, 2019)
(Title: Fukugoukakujoshi To Doujini and To Tomoni in the Japanese Language) To doujini and to tomoni in Japanese are fukugoukakujoshi (compound particles) which are both used to express two things that occur or take place simultaneously. The purpose of this study is to describe the structure and meaning of fukugoukakujoshi to doujini and to tomoni in Japanese sentences. The method used in this research is Agih with Bagi Unsur Langsung techniques. Based on research it is known that structurally to doujini and to tomoni can be attached to verbs, adjectives, and nouns. In terms of to doujini it has three meanings, that was ‘at the same time’, ‘immediately after’, and ‘and also’; to tomoni also has three meanings, that was ‘at the same time’, ‘along with’, and ‘together with’.